Analysis of the opportunities for developement the rural tourism supply on mountain Skopska Crna Gora - Julijana Petrovska; Marina Stojmirova; Jovo Ratkovic (UTMS Journal of Economics, 2014)
Macedonia, as a future member of the European Union, is facing an important and difficult task: to promote its tourism supply according to the leading European Countries in order to achieve competitive advantage in tourism market. Alternative forms of tourism are an important part of a tourism supply that could satisfy the specific tourist needs. These include rural tourism for which there is an increased demand every day. Macedonia is a country rich in various resources that are essential for making unique, rich and competent rural tourism supply, created strictly according to the principles of sustainable development. The aim of this paper work is to indicate the importance of the development of rural tourism supply for Macedonia, whereas the objective is to analyze the possibilities of the development of the rural tourism supply in the area of mountain Skopska Crna Gora, in order to develop competitive tourism supply.
Keywords: Q5; 330; rural tourism; Mountain Skopska; Crna Gora